PENGARUH PEMBERIAN NPK PHONSKA DAN KOTORAN AYAM TERHADAP PERTUMBUHAN DAN HASIL JAGUNG MANIS (Zea mays Saccharata Sturt) - Eka Rahmawati; Karno; Widya Saputra (Jurnal Magrobis, 2022)
This study aimed to determine the effect of NPK phonska fertilizer and chicken manure on the growth and yield of sweet corn (Zea mays Saccharata Sturt). This research started from November 2021 to January 2022, carried out in Jonggon Jaya village, Loa Kulu Sub District, Kutai Kartanegara Regency, East Kalimantan Province. The study was arranged in a Factorial Randomized Complete Block Design (RCBD) consisting of 2 factors and repeated three times. The first factor was Phonska NPK fertilizer (p), which consisted of four levels, namely p0 (without treatment), p1 (150 kg ha-1), p2 (300 kg ha-1), p3 (450 kg ha-1). The second factor was the application of chicken manure (s) which consisted of four levels, namely s0 (without treatment), s1 (10 t ha-1), s2 (20 t ha-1) and s3 (30 t ha-1). The results showed that Phonska NPK fertilizer had no significant effect on all observation parameters. The highest average yield on cob weight per hectare was p1 (150 kg ha-1) 14.07 t ha-1. Meanwhile, for the lowest treatment, the average weight of cob weight per hectare was 12.96 t ha-1, namely in treatment p2 (300 kg ha-1). The results showed that chicken manure had no significant effect on all observation parameters. The highest average yield on cob weight per hectare was s1 (10 tons ha-1) 14.17 t ha-1. Meanwhile, for the lowest treatment, the average weight of cob weight per hectare was 13.09 t ha-1, namely the s3 treatment (30 tons ha-1). The results of the interaction between NPK phonska fertilizer and chicken manure had no significant effect on all observation parameters. The highest yield of cob weight per hectare was in the s2p1 treatment with an average yield of 14.83 t ha-1 and the lowest yield of cob weight per hectare was in the s3p2 treatment with an average yield of 9.52 t ha-1.